Polycentric port governance. (November 2019) - Monios, Jason
Abstract: This paper applies the theory of polycentric governance to the port sector. The paper demonstrates that port governance is already polycentric, including a variety of actors at different scales with overlapping jurisdictions, but some of the established principles of effective polycentric governance such as collective choice arrangements and distribution of costs are not currently in place. This has resulted in an inability to manage current challenges, which can be broadly divided into environmental challenges (emissions and other pollution, adapting to climate change impacts such as sea level rise and storms) and port investment challenges (conflicts related to port capacity developments). Current static models of port governance exhibit an over-emphasis on hierarchy and internal, formal structures (mostly government, port authority and port terminal operator), whereas a polycentric approach favours explicitly including informal organisations (e.g. citizen and environmental groups) and external actors (e.g. carriers, shipping regulators) in a more dynamic conceptualisation. This enables an application of the known strengths and weaknesses of polycentric governance to the port sector, in order to identify where some of the known measures for successful polycentric governance should be implemented. The paper also feeds back to the theory on polycentric governance regarding the challenges of including global actors within territorial polycentric regimes. Highlights: Applies the theory of polycentric governance to the port sector. Port governance includes a variety of actors at different scales with overlapping jurisdictions. Established principles of effective polycentric governance are not currently in place. Current static models of port governance exhibit an over-emphasis on hierarchy and internal, formal structures. A polycentric approach favours explicitly including informal organisations and external actors.